Pengaruh Temuan Kepatuhan, Tindak Lanjut Hasil Pemeriksaan Dan Temuan Sistem Pengendalian Internal Terhadap Opini Audit Laporan Keuangan (Studi Empiris BPK Perwakilan Provinsi Jambi Pada Kabupaten dan Kota di Provinsi Jambi Tahun 2019 - 2023) - Kusmiati; Desy Purwasih (Jurnal Akuntansi Keuangan dan Bisnis, 2024)
This research was conducted to analyze the influence of Compliance, Follow-up on Audit Results Internal Control System Findings on Audit Opinions. The research was conducted in districts and cities in Jambi Province, the Financial Audit Agency (BPK) representing Jambi Province in 2019-2023. The methodology used is logistic regression because the dependent variable of the research is a dummy. Sample selection was carried out using a boring sampling method from secondary data in the form of Regency and City financial reports at the Representative BPK of Jambi Province with 5 years of observation, so that in total in this research there were 60 financial reports. Hypothesis testing was carried out using the Eviews series 12 application. The research results showed that partially the attendance findings had no effect on the audit opinion. Follow-up examination results have no effect on the audit opinion. The internal control system has no effect on the audit opinion. Simultaneously, these findings, follow-up audit results and internal control system findings influence the financial report audit opinion.